NARSISTIK GAY STYLE PADA TIKTOK:(Etnografi Virtual Komunikasi Verbal Melalui Media TikTok Dalam Perspektif Computer Mediated Communications) - Rakha Fary Novyan (2022)
This study aims to understand how the virtual communication culture is shaped by gays through narcissistic actions on TikTok social media and to understand the message that gays convey through video content on TikTok social media. The method used in this research is descriptive qualitative. Data collection used interview techniques and observation of TikTok content created by gay people with a sampling method using snowball sampling. To examine it, this study uses CMC and Queer theories. Data analysis techniques use taxonomic techniques that aim to clarify terms or behavioral segments of a particular domain to find out how they are systematically grouped or linked. The results of this study say that sexual identity is dynamic and the TikTok content created by gay people is a form of self-disclosure so that they are considered to exist in society. With this content, they want to create a friendly, expressive, and humorous character, and they also want to convey the message that all people have the same rights, are not distinguished between gay and those who are not, being gay is not as bad as what society thinks and they hope that society can accept a difference without making a difference.